PENGARUH KEPUASAN KERJA DAN PENGAWASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. TRIJAYA PRATAMA FUTURES MEDAN (PERUSAHAAN YANG BERGERAK DI BIDANG BERJANGKA) - Edo Tantono (JURNAL MANAJEMEN, 2019)
The purpose of the study is to analyze the effect of job satisfaction and work supervision on the employee performance at PT Trijaya Pratama Futures Medan. The method used in this study is a quantitative approach. The method of data collection is done by interviews, questionnaires, and documentation. The data analysis method used is a multiple linear regression. The population and sample are 68 employees. The results showed that simultaneously and partially job satisfaction and work supervision have a positive and significant effect on employee performance at PT. Trijaya Pratama Futures Medan.